c-fos Geni ve Fos Proteinleri - KEKLİKOĞLU, Nurullah (Cerrahpaşa Medical Journal, 2014)
Background.- c-fos is a gene that is transcribed temporarily and rapidly by factors that cause growth and differentiation by affecting cells. Fos proteins are nuclear proteins that are produced by c-fos gene. c-fos is considered to be a third nuclear messenger. The expression and accumulation of c-fos gene, a protooncogen that is a member of IEG (Immediate Early Gene) group, and Fos proteins, a member of AP-1 (Activator Protein-1) family oncoproteins, upsurge along with cellular activation under the affect of certain stimuli. This gene and proteins play a very important role during cellular proliferation, differentiation and programmed cell death (apoptosis). The c-fos gene and Fos proteins, being a potential activator of transcription, are a key to understand congenital anomalies, oncogenic transformation and normal development due to their relationship with abovementioned biological processes.